Length-Weight Relationship of the Toothed Pony Fish, Gazza Minuta (Bloch, 1797) from Tuticorin Waters of India - Puvaneswari, S.; Karuppasamy, R. (International Journal of Scientific Research in Biological Sciences, 2019)
Length-weight analysis for specimen comprising 494 males, 515 females and indeterminants of Gazza minuta, collected from Tuticorin fish landing centre was made to assess the relationship between the variables The length-weight relationship was estimated using the exponential equation W = aLn for one species of pony fish belonging to family leiognathidae, species Gazza minuta, in the catches of tuticorin landing centre . The correlation co-efficient (“r” values) of male, female and indeterminants were found to be 0.9750 (p<0.001), 0.9800 (p<0.001) and 0.8931(p<0.001) respectively. Length-weight relationship study in G. minuta obeys cube law, particularly in the adults.